(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses the role and place of the ideals of humanism as well as tolerance in the development of ethics, culture, humanistic qualities of young people who are the leading forces of our society. There are ideas about the wide use of the scientific heritage of the scientists and thinkers in the life of youth.